Bralni okus Slovencev in njegove posledice - Radetič, Andreja (Vestnik za tuje jezike, 2010)
Firstly, the importance and positive impacts of reading are listed: better comprehension of personal experience, development of linguistic skills etc. Further on, the article focuses on trivial literature: its definition and statistical data of borrowings in Slovene libraries in summer months 2010. Negative influences of reading trivial literature, especially on children, are enumerated. Most of them are noticed in the author's classes: stereotypic image of the world, poorer capabilities of critical thought and knowledge of linguistic means; also impact on subconscious, and following the example of inappropriate literary characters. At the end, the author speculates on possible reasons for such a reading choice.
Keywords: branje; trivialna literatura; Slovenia; Slovenija